(untitled) (Konferensiyalar | Conferences, 2024)
We know that using technologies in teaching English is absolutely vital during the lesson in Uzbekistan. This article presents a theoretical and methodological model of application wiki technologies for the development of written and speech skills of non-linguistic student‘s university issues related to the relationship of participants are considered educational process in the conditions of informatization of education; this article discusses some problems in using wiki technologies at school and universities; and their solutions to problems.